2017
DOI: 10.1016/j.biopsych.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Central Ghrelin Resistance Permits the Overconsolidation of Fear Memory

Abstract: Background There are many contradictory findings on the role of the hormone ghrelin in aversive processing, with studies suggesting that ghrelin signaling can both inhibit and enhance aversion. Here, we characterize and reconcile the paradoxical role of ghrelin in the acquisition of fearful memories. Methods We used enzyme-linked immunosorbent assay (ELISA) to measure endogenous acyl-ghrelin and corticosterone at time points surrounding auditory fear learning. We used pharmacological (systemic and intra-amyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 72 publications
1
59
1
Order By: Relevance
“…This is likely a result of the different mechanisms of action of ghrelin/GHSR signalling with respect to controlling different memory domains encoded by different brain circuits. By contrast to the control of hippocampal‐dependent spatial memory, which may involve neuroinflammation and synaptic plasticity based on our data, the ghrelin/GHSR‐mediated control of the consolidation of contextual fear memory instead requires the down‐regulation of GHSR in the amygdala . The effect of endogenous ghrelin on olfactory memory might involve a different mechanism, such as ghrelin‐induced neurogenesis, which is known to affect olfactory discrimination .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This is likely a result of the different mechanisms of action of ghrelin/GHSR signalling with respect to controlling different memory domains encoded by different brain circuits. By contrast to the control of hippocampal‐dependent spatial memory, which may involve neuroinflammation and synaptic plasticity based on our data, the ghrelin/GHSR‐mediated control of the consolidation of contextual fear memory instead requires the down‐regulation of GHSR in the amygdala . The effect of endogenous ghrelin on olfactory memory might involve a different mechanism, such as ghrelin‐induced neurogenesis, which is known to affect olfactory discrimination .…”
Section: Discussionmentioning
confidence: 58%
“…Considering the important role of ghrelin and GHSR signalling in conveying energy deficit, it is likely that ghrelin/GHSR signalling in the hippocampus enhances spatial learning to promote re‐feeding and restoration of energy balance . However, this ghrelin/GHSR signalling may operate differently in different brain regions because contextual fear memory is also dependent on GHSR but is independent of energy balance …”
Section: Discussionmentioning
confidence: 99%
“…GHSR-1a is expressed in all three components of the dorsal vagal complex, and central administration of ghrelin to rodents recapitulates some of these actions of the hormone [31,32,33]; however, the extent to which these effects of ghrelin depend on its action at central level in humans is currently uncertain. Finally, it is interesting to stress that studies in rodents have shown that ghrelin system also impacts on higher cognitive functions, such as learning and memory, but the implications of these studies in humans are currently unclear [34,35]. …”
Section: Introductionmentioning
confidence: 99%
“…Obesity-dependent ghrelin resistance will suppress these antidepressant and neuroprotective effects (Lutter et al, 2008), promoting MDD. Recent animal studies indicate stressrelated ghrelin resistance also contributes to amygdala hyperactivation and overconsolidation of fear memories, independent of appetite responses (Harmatz et al, 2017).…”
Section: Leptin and Ghrelinmentioning
confidence: 99%